A New Social Question? On Minimum Income Protection in the Postindustrial Era - Marx, Ive (Changing Welfare States, 2007)
Advanced welfare states are said to be facing, in the words of Pierre Rosanvallon, a "New Social Question". The idea here, and it is a widely shared one, is that the transition from an industrial to a postindustrial environment has brought with it a whole new set of social risks, constraints and trade-offs which necessitate radical recalibration of social security systems. This book analyses in some depth how economic change has impacted on minimum income protection in advanced welfare states. There is a particular focus on how Bismarckian welfare states have fared over recent decades. This title is available in the OAPEN Library - http://www.oapen.org.